2011
DOI: 10.4103/0972-124x.85661
|View full text |Cite
|
Sign up to set email alerts
|

Aloe vera: Nature′s soothing healer to periodontal disease

Abstract: Background:Recent interest and advances in the field of alternative medicine has promoted the use of various herbal and natural products for multiple uses in the field of medicine. Aloe vera is one such product exhibiting multiple benefits and has gained considerable importance in clinical research. This clinical study focuses on Aloe vera and highlights its property when used as a medicament in the periodontal pocket.Materials and Methods:A total number of 15 subjects were evaluated for clinical parameters li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
20

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 39 publications
3
66
0
20
Order By: Relevance
“…Clinically proven studies have showed that mouthrinses and dentifrices containing aloe vera have shown a remarkable reduction in gingivitis and plaque accumulation after its use [15,16]. Studies by Geetha Bhatt et al, have proved the use of aloe vera gel as a subgingivasl administrator in the treatment of periodontal pockets [17].…”
Section: Aloe Vera and Dentistrymentioning
confidence: 99%
“…Clinically proven studies have showed that mouthrinses and dentifrices containing aloe vera have shown a remarkable reduction in gingivitis and plaque accumulation after its use [15,16]. Studies by Geetha Bhatt et al, have proved the use of aloe vera gel as a subgingivasl administrator in the treatment of periodontal pockets [17].…”
Section: Aloe Vera and Dentistrymentioning
confidence: 99%
“…[44,45] The research of specific activity demonstrated that gel has strong periodontium protecting antimicrobial, anti-inflammatory, and reparative properties.…”
Section: Technological Processmentioning
confidence: 99%
“…Periodontitis: Bhat G et al [18] evaluated the effects of subgingival application of Aloe vera gel in periodontal pockets of adult periodontitis patients after mechanical debridement. In his study, 15 subjects were evaluated for clinical parameters such as plaque index, gingival index, probing pocket depth at baseline, followed by scaling and root planning.…”
Section: World Journal Of Pharmaceutical Researchmentioning
confidence: 99%
“…Advantages of Aloe vera [4] Aloe vera can be used as a local drug delivery system because of its various benefits …”
Section: World Journal Of Pharmaceutical Researchmentioning
confidence: 99%